Project level assessment of indirect land use changes arising from biofuel production. Issue 11 (21st September 2019) - Di Lucia, Lorenzo; Sevigné‐Itoiz, Eva; Peterson, Steve; Bauen, Ausilio; Slade, Raphael
Abstract: The use of land resources has a strong influence on the sustainability of biofuel production. An assessment of both direct and indirect changes in land use is necessary if an accurate assessment of sustainability is to be made. An increasing number of studies have developed approaches to estimate the Indirect Land Use Change (ILUC) impacts of biofuels at global, national or regional level, but assessing ILUC remains a challenging task and estimates vary widely. In this study, we suggest that a socially motivated, project level approach can provide robust insight into the conditions affecting land use change dynamics. We developed a causal‐descriptive approach named ILUC Project ASsessment Tool (ILUC PAST) for project level assessment of ILUC. It uses a tiered multitool analysis—from local to global—combined with extensive stakeholder engagement. A real‐world project for the production of cellulosic ethanol in Sardinia (Italy) was used to evaluate the tool and benchmark the results against two alternatives for project level assessment: the 'Low Indirect Impact Biofuel' methodology and the 'iLUC Club' method. The results of the case study of advanced biofuels suggest that the quantitative estimates of ILUC combined with the in‐depth understanding of the cause‐and‐effect dynamics provided by ILUC PAST are sufficiently credible, salient and legitimate to support project level and local decision‐making. Abstract : Unlocking the potential benefits of biomass‐based energy production requires new approaches to support decision‐making with robust information about impacts on land resources. ILUC‐PAST is a Causal Descriptive method we developed to calculate the ILUC associated with individual biofuel projects. Combining spatial explicit data analysis, System Dynamics modelling and engagement of local actors, it quantifies ILUC and identifies mitigation options. The method was applied to evaluate a commercial scale project for advanced ethanol production in Sardinia, Italy, and compared against two alternative methodologies. The results provide an assessment of land use dynamics that is more credible, legitimate and salient.